OPINI AUDIT GOING CONCERN – KAJIAN BERDASARKAN FINANCIAL DISTRESS, PRIOR OPINION, AUDIT FIRM REPUTATION, DAN DEBT DEFAULT PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - B2091171013, THOMAS AVERIO (MAKSI UNTAN, 2019)
Based assumption of going concern opinion used by the auditor to prepare financial statements. Assumption appears if the auditor has a doubt of financial statements. Going concern audit opinion provision may worsen the company likes loss of public confidence even go bankrupt. This study aimed to determine the effect of financial distress, prior opinion, audit firm reputation, and debt default of the company of Going Concern Audit Opinion. This research used purposive sampling method with some criterias and the sample was about 29 companies. Analyzed by logistic regression and test using program SPSS 24.0 for windows concluded that prior opinion, audit firm reputation, and debt default don’t have effect on acceptance of going concern audit opinion, but the one that have effect on going concern audit opinion is financial distress.Keywords : Going Concern, Financial Distress, Prior Opinion, Audit Firm Reputation, Debt Default, Audit OpinionDAFTAR PUSTAKAAryantika, Ni Putu., dan Rasmini, Ni Ketut. (2015). Profitabilitas, Leverage, Prior Opinion Dan Kompetensi Auditor Pada Opini Audit Going Concern. E-Jurnal Akuntasi Universitas Udayana 11.2: 414-425. Astari, Putu W., dan Latrini, Made Y. (2017). Faktor-Faktor Yang Mempengaruhi Penerimaan Opini Audit Going Concern. E-Jurnal Akuntansi Universitas Udayana, Vol.19.3:2407-2438. Azizah, Rizki., dan Anisykurlillah, Indah. (2014). Pengaruh Ukuran Perusahaan, Debt Default, Dan Kondisi Keuangan Perusahaan Terhadap Penerimaan Opini Audit Going Concern. Accounting Analysis Journal 3.4: 533-542. Dewi, I Dewa., dan Latrini, Made Yenni. (2018). Pengaruh Financial Distress Dan Debt Default Pada Opini Audit Going Concern. E-Jurnal Akuntansi Universitas Udayana Vol.22.2: 1223-1252. Haron, et al. (2009). Factor Influencing Auditor’s Going Concern Opinion. Asian Academy of Management Journal, Vol.14 No.1:1-19.Ikatan Akuntan Indonesia. (2001). Standar Profesional Akuntan Publik. Jakarta:Salemba Empat. Jamaluddin. (2018). The Effect Of Financial Distress And Disclosure On Going Concern Opinion Of The Banking Company Listing In Indonesian Stock Exchange. International Journal Of Scientific Research And Management Vol.06. Jensen, M.C., & Meckling, W. (1976). Theory of the firm: Managerial behavior, agency cost and ownership structure. Journal of Financial Economics, 3. 305-360. Kartika, Andi. (2012). Pengaruh Kondisi Keuangan dan Non Keuangan Terhadap Penerimaan Opini Going Concern pada Perusahaan Manufaktur di BEI. Jurnal Dinamika Akuntansi, Keuangan, dan Perbankan, Vol.1 No.1:25-40. Nariman, Augustpaosa. (2015). Pengaruh Ukuran Kantor Akuntan Publik Terhadap Opini Going Concern Dan Earnings Response Coefficients (Erc) Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Tahun 2011-2013. Jurnal Akuntansi Universitas Tarumanegara, 19(2):160-178. Praptitorini, M.D., & I. Januarti. (2007). Analisis Pengaruh Kualitas Audit, Debt Default, Dan Opinion Shopping Terhadap Penerimaan Opini Going Concern. Prosiding, Disampaikan Dalam Simposium Nasional Akuntansi X. Makassar.Rahim, Syamsuri. (2016). Pengaruh Kondisi Keuangan Perusahaan, Kualitas Audit Dan Opinion Shopping Terhadap Penerimaan Opini Going Concern. Jurnal Ilmiah Akuntansi Dan Bisnis, Vol. 11, No. 2. Ramadhani, Karina. (2016). Variabel-Variabel Yang Memengaruhi Penerimaan Opini Audit Going Concern pada Perusahaan LQ45 yang Terdaftar di BEI Tahun 2013-2014. Universitas Kanjuruhan Malang.Susanto, Yulius Kurnia. (2009). Pengaruh Reputasi Auditor, Disclosure, Ukuran Perusahaan Dan Opini Audit Tahun Sebelumnya Terhadap Penerimaan Opini Audit Going Concern. Jurnal Bisnis Dan Akuntansi Vol 11, No 3. Sekolah Tinggi Ilmu Ekonomi. Trisakti Tandungan, Debby. dan Mertha, I Made. (2016). Pengaruh Komite Audit, Ukuran Perusahaan, Audit Tenure, Dan Reputasi KAP Terhadap Opini Audit Going Concern. E-Jurnal Akuntansi Universitas Udayana Vol.16.1:45-71. Venuti, E. K. (2007). The Going Concern Assumption Revisted: Assesing A Company’s Future Viability. The CPA Journal Online, 74(5):40-43. Yaqin, Muhammad Ainun., Dan Sari, Maria. (2015). Pengaruh Faktor Keuangan Dan Non Keuangan Pada Opini Audit Going Concern. E-Jurnal Akuntansi Universitas Udayana 11.2: 500-514